2014
DOI: 10.1007/s00068-014-0455-y
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and clinical practice for the detection and management of trauma-associated haemorrhage and coagulopathy

Abstract: This study confirms differences in infrastructure, logistics and clinical practice for the detection and management of trauma-haemorrhage and trauma-associated coagulopathy amongst international centres. Ongoing work will focus on geographical differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Persistent higher odds for osteoporosis therapy after 120 days of follow-up confirmed these findings. This is in line with previous studies, which demonstrated that differences in infrastructure, logistics and clinical practice in the management of trauma patients have significant impact on patients outcome [ 28 ]. Interestingly, no influence of geriatric treatment frequency was observed on in-house mortality and after 120 days of follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Persistent higher odds for osteoporosis therapy after 120 days of follow-up confirmed these findings. This is in line with previous studies, which demonstrated that differences in infrastructure, logistics and clinical practice in the management of trauma patients have significant impact on patients outcome [ 28 ]. Interestingly, no influence of geriatric treatment frequency was observed on in-house mortality and after 120 days of follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Besides the early recognition of coagulopathy and severe shock, early initiated goal-directed transfusion management is crucial [35,36]. In the present study, 30-40% coagulopathic children received blood products independent of age.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, there is a large diversity in the clinical management of major bleeding events even among advanced trauma centers. 33 There is still a controversy whether the empiric administration of blood products in predefined and fixed ratios (cf. damage control resuscitation [DCR]) might be superior to global coagulation testing in acute setting of trauma to enable goal-directed strategies.…”
Section: Scenario 1: Coagulopathy Following Major Trauma: Goal-direct...mentioning
confidence: 99%